Untersuchungen zu Schwankungen der Konvektionsaktivität in Labradorsee und Irminger See - 1997 - 2009 - - Kopte, Robert (2011)
Interannual to seasonal variability of convective activity is investigated in both Labrador and Irminger Seas between 1997 and 2009. Possible reasons for these variabilities and their direct consequences for the convection basins are discussed. Long-time data, collected by moorings K1 (central Labrador Sea) and CIS (central Irminger Sea), was used for analysis of wintertime Mixed Layer Depths and temperature developments, supported by ARGO data from profiles taken within the convective regions closely matching to the moorings. Furthermore a dataset, provided by the NCEP/NCAR reanalysis project served the examination of net heat fluxes through the air-sea interface to determine the role of atmospheric forcing for the convective process. There is no indication for an upcoming phase of enhanced convective activity following the 2008 event, when surprisingly deep-reaching convection to depths of approx. 1800m, triggered by massive atmospheric forcing, took place after several winters of rather weak convection. As one consequence the warming trend in the intermediate water layers was disrupted just shortly in 2008, but has been ongoing with similiar intensity since. However, it is expected that there is a consistent horizontal input of heat into the central Labrador Sea, partially compensating massive heat losses during the convective season. Compared to the Larbador Sea, convection in the Irminger Sea generally is less deepreaching, because of differences in atmospheric excitation. It did not exceed 1000m during the investigated period. Hence it can be concluded that there possibly was no contribution in the formation of Labrador Sea Water by convective activities in the Irminger Sea during that time.